2010
DOI: 10.3109/02688691003675218
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of chronic subdural haematomas – A retrospective comparison of minicraniectomy versus burrhole drainage

Abstract: Primary chronic subdural haematomas remains one of the commonest conditions managed by neurosurgeons. Despite this there is a relative lack of evidence regarding best management and certain treatments such as minicraniectomy, have rarely been assessed in the literature. A retrospective case note review comparing minicraniectomy and burrhole drainage of primary chronic subdural haematoma was therefore performed. We sought to determine the proportion of patients requiring repeat drainage or dandy cannula aspirat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 9 publications
1
16
0
3
Order By: Relevance
“…Despite these concerns, the frequency of a trauma history (head injury or fall, M:F 50% vs. 57% -the second largest risk factor) compared favourably with 56% reported by Ramachandran et al [18] in a much larger series of 647 CSDH cases. Furthermore, a history of alcohol abuse/dependence (M:F 17% vs. 16%) was also of a similar order to that reported in other studies (11-24%) [19][20][21].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Despite these concerns, the frequency of a trauma history (head injury or fall, M:F 50% vs. 57% -the second largest risk factor) compared favourably with 56% reported by Ramachandran et al [18] in a much larger series of 647 CSDH cases. Furthermore, a history of alcohol abuse/dependence (M:F 17% vs. 16%) was also of a similar order to that reported in other studies (11-24%) [19][20][21].…”
Section: Discussionsupporting
confidence: 78%
“…In particular, there was no significant gender difference in either a history of trauma (head injury or fall) (P = 0.37) or alcohol abuse/dependence/intoxication (P = 0.89). Indeed, frequencies for alcohol abuse/dependence of 11-24% [19][20][21] render it improbable that this risk factor alone could ever explain a 2:1 male bias. Traditional assumptions therefore appear unsound.…”
Section: Discussionmentioning
confidence: 95%
“…Four of these studies were prospective, the remaining ten were retrospective. Six compared TDC to BHC [21,26,61,74,83,98], one compared TDC to a combined group of BHC and craniotomy [36], and the other seven compared BHC to craniotomy [14,29,48,52,60,87,97]. The studies evaluated suggest that TDC may be superior to BHC in terms of infection rate [83], but worse in terms of the proportion of patients that developed signs of clinical deterioration [98].…”
Section: Relative Safety and Efficacy Of The Various Csdh Evacuation mentioning
confidence: 92%
“…Two studies report a 0% rate of recurrence with this technique (Table 2) [6,87]; however, the rate of re-operation from other studies ranged between 12% and 23% [14,48]. Mortality following craniotomy has been reported between 0% and 17% [6,87,97], while mortality of groups combining BHC and craniotomy were between 5% and 13% [36,48]. No studies have specifically examined complication rates in a group of craniotomy-treated patients.…”
Section: Relative Safety and Efficacy Of The Various Csdh Evacuation mentioning
confidence: 92%
“…Craniotomy remains a valid and safe technique for the management of older patients with emergent intracranial bleeds 14 and is particularly important 37 and successful in treating elderly patients, 7 but is an expensive procedure. 21 It has been reported that the average craniotomy procedure itself costs $15,867 at high-volume centers.…”
Section: (Continued)mentioning
confidence: 99%